Ensuring Nutritional Security of Animals by Mixed Cropping of Sorghum and Guar under Varying Nutrient Management - Bhakar, Ankur; Singh, Magan; Kumar, Sanjeev; Dutta, Susanta; Mahanta, Ranajit Kumar; Onte, Santosh (Indian Journal of Animal Nutrition, 2020)
An experiment was carried out to analyse productivity and quality of fodder sorghum and guar as influenced by nutrient management under mixed cropping and in kharif season of 2018 tested in factorial randomized complete block design with four seed rate combinations of sorghum and guar along with six nutrient management treatments in three replications. The productivity of crops was evaluated in terms of fodder yield and quality in form of dry matter, organic matter, ash, crude protein, ether extract, total carbohydrates, fibre fractions (NDF, ADF, ADL and hemicellulose), total digestible nutrients, dry matter intake and dry matter digestibility. Results revealed that total green fodder and dry matter yield was higher in sole sorghum but it was at par with 75% sorghum + 25% guar. Mixed cropping treatments performed better in comparison to sole crops for different quality parameters in both crops. Among nutrient management, treatments 100% RDF, 100% RDF+ PGPR and 100% RDF+ seaweed extract recorded higher fodder production as well as fodder quality in both crops which was not statistically different from75% RDF + seaweed extract treatment. The results revealed that seed rate of 75% sorghum + 25% guar in mixed cropping with the application of 75% RDF + seaweed extract produced higher quality fodder for animals.